Canada : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This Informational Annex highlights the Canadian authorities' free-floating exchange rate regime. The exchange rate regime is free from exchange restrictions and multiple currency practices. The Canadian authorities do not maintain margins with respect to exchange transactions. However, the authorities may intervene to ensure orderly conditions in the exchange market. There are no taxes or subsidies on purchases or sales of foreign exchange. Canada's exchange system is free of restrictions on the making of payments and transfers for current international transactions. Canada also maintains exchange restrictions for security reasons, based on UN Security Council resolutions reported to the IMF for approval.